SOCIALIZATION OF CORAL REEF SUSTAINABILITY IN PARI CAY, SERIBU ISLANDS - Firman Herdiansyah; Ali Jambak; Dewi Syavitri; Surya Darma Hafiz (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2019)
Pari Cay was known as one of significant growth of coral reef area for marine ecosystem. Pari Cay belongs to the Seribu Islands which is located in the Jakarta Bay. The islands are formed from the assemblage of marine biota assemblage. Coral reefs are a comfortable environment for the life of various underwater biota which must be preserved and protected from damage and extinction. Fish catches of fishers in Jakarta Bay are strongly influenced by the preserved of the surrounding coral reefs. The reduced number of coral reefs will reduce the catch of fishermen's fish. Through this socialization is expected that citizens can take part and participate in preserving the marine and coastal environment, especially Pari Cay coral reefs. The increasing participation of the surrounding inhabitant in marine life sustainability is expected to improve the livelihoods of the communities both from fishing and tourism. The society enthusiasm of the Pari Island with this socialization at least can find out the desire of the Pari Island Citizens to preserve the coral reefs. These a continuation of the previous socialization and changes in the awareness of the Pari Island Citizens to preserving coral reefs have been look significant.